Site classification for soft soil at the east coast petrochemical industrial corridor / Mohd Farid Ahmad @ Majid, Shakirah Mohd Abdul Rahman and Rofiza Aboo Bakar - Ahmad @ Majid, Mohd Farid; Mohd Abdul Rahman, Shakirah; Aboo Bakar, Rofiza (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2005)
The east coast industrial corridor is located between Gebeng in Pahang to Paka in Terengganu. Based on study conducted, the geology of the area consisted of beach ridges formed by the storm wave action of South China Sea. Further, for this study soil boring and CPT tests were conducted. For sampling, special sampling equipment was fabricated to sample the sandy soil. Sieve analysis conducted found the soil to be silty sand of Poorly Graded Sand (SP) or Well Graded Sand (SW). Classification from CPT test could only provide indication of soil type present. Direct shear test conducted found the sandy soil to have internal angle of friction of around 30 degrees. The results of shear strength parameters (C and 0) from direct shear test was then compared with values obtained correlated using equation by Campanella and Robertson (1983). The result of comparison found that the equation by Campanella and Robertson would give higher 0 values than the direct shear test. The values would closer if C values is 0 (zero). This indicate presents of cohesion, C, reduced the accuracy of the equation.